2021
DOI: 10.1109/access.2021.3058517
|View full text |Cite
|
Sign up to set email alerts
|

Prefeasibility Economic and Sensitivity Assessment of Hybrid Renewable Energy System

Abstract: Nowadays, microgrids with hybrid renewable energy sources are increasing, and it is a promising solution to electrify remote areas where distribution network expansion is not feasible or economical. This study aims to find an ideal hybrid system grounded on solar, wind, diesel, biomass, hydro, and battery. This study utilizes the hybrid optimization model for electric renewable (HOMER) software to size the important components, perform technical, financial evaluation, renewable factor, estimate the harmful emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Data available on request from the authors. Most of data that support the findings of this work are included in the paper or cited in the References 4,5,17,18,30,32‐35,37,38. Some of data are available on request from the corresponding author (Details about different types of solar panel specification available at: https://kenbrooksolar.com/solar-panel/300-watt-solar-panel).…”
Section: Peer Reviewmentioning
confidence: 91%
“…Data available on request from the authors. Most of data that support the findings of this work are included in the paper or cited in the References 4,5,17,18,30,32‐35,37,38. Some of data are available on request from the corresponding author (Details about different types of solar panel specification available at: https://kenbrooksolar.com/solar-panel/300-watt-solar-panel).…”
Section: Peer Reviewmentioning
confidence: 91%
“…Many researchers and studies have investigated hybrid renewable energy systems, and from different perspectives, such as energy management systems [13], demand response [14], economic cost [15], carbon dioxide emissions and environmental impact [16], optimizing source size [17,18], communication network [19,20], IoT-enabled smart grid [21][22][23], HRES optimization [24,25], modeling based on international standards [26][27][28][29], optimal location [30], and capacity planning [31]. The author in [13] provided an overview of energy management agent (EMA) framework architectures' ability to manage the energy generation/consumption of DERs/HRES in homes, buildings, and communities.…”
Section: Related Workmentioning
confidence: 99%
“…A case study of a Tunisian petroleum platform has been considered to evaluate a proposed optimization solution. Authors in [18] showed the viability of HRES for isolated urban electrification in India. The HOMER software has been used for sizing the system and perform the technical and financial evaluation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…An artificial neural network (ANN) is the piece of a computing system designed to simulate the way the human brain analyzes and processes information. It is the foundation of artificial intelligence (AI) and solves problems that would prove impossible or difficult by human or statistical standard [13,[17][18][19][20].…”
Section: Artificial Neural Networkmentioning
confidence: 99%